2012
DOI: 10.3233/wor-2012-1356
|View full text |Cite
|
Sign up to set email alerts
|

Exploring workplace related health resources from a salutogenic perspective: Results from a focus group study among healthcare workers in Sweden

Abstract: The aim of this study was to explore healthcare workers' opinions on workplace related health resources relevant to promotion of their health. Participants: 16 registered nurses and 19 assistant nurses, from a medical emergency ward at a medium sized hospital in the south of Sweden, participated in the study. Methods: Eight focus group interviews were conducted, the material was condensed and conventional qualitative content analysis was used to elicit and identify patterns in the expressed opinions of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
(51 reference statements)
2
38
0
3
Order By: Relevance
“…Bringsén et al showed that occupational health in general must focus more on health promotion 3. To work with health promotion with a salutogenic approach can be the future for OHSs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bringsén et al showed that occupational health in general must focus more on health promotion 3. To work with health promotion with a salutogenic approach can be the future for OHSs.…”
Section: Discussionmentioning
confidence: 99%
“…They pointed out how important it is that the occupational health professional visit the companies more frequently for meetings and discussions with the employees. This can be in a salutogenic approach making employees feel involved and included 3. The managers wanted more education regarding work environment, and this is something that the OHSC should develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the ways relationships at work can serve as a resource for creating a sustainable workplace that improves and maintains well-being among employees is needed (Brings en, Andersson, Ejlertsson, & Troein, 2012;Bronkhorst, Tummers, Steijn, & Vijverberg, 2015;Nilsson, Andersson, Ejlertsson, & Troein, 2012;Umberson & Montez, 2010;Zhang, Punnett, & Gore, 2014). As relationships occur in many parts of healthcare work, efforts to identify relationships and social climate among healthcare workers may be vital for employee well-being (Ljungblad, Granstr€ om, Dellve, & Akerlind, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An open communication climate is essential to achieve a better work environment [6] and it can therefore be regarded as health-promoting as it strengthens conditions for employee to exert influence and became involved [7]. …”
Section: Introductionmentioning
confidence: 99%